Trees with High Wood Carbon is a Good Source of Bioenergy and Sink of Atmospheric Carbon Dioxide: a Viable Strategy to Reduce Carbon Pollution - Maiti, Ratikanta; Rodriguez, Humberto Gonzalez (International Journal of Bio-resource and Stress Management, 2019)
Increasing global warming with constant emission of carbon dioxide (CO2) owing to burning of fossil fuels has reached alarming situation to he scientists. Different strategies are adopted throughout World to reduce atmospheric carbon pollution. Forest trees have good capacity to capture CO2 through leaves and solar energy during the process of photosynthesis. Finally carbon is stored in aerial parts and woods. Therefore, a viable strategy is the extensive plantation of trees in factory areas as well as city streets. Various studies are also undertaken in different countries in this direct to curb this global menace. In advanced countries, emitting CO2 is captured with instrument and then pushed deep in soil where it is stored for long time...